2022
DOI: 10.47815/apsr.2022.10137
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability estimates and gene action studies from full diallel mating design in maize (Zea mays L.)

Abstract: A study was under taken during kharif season of 2016 at College of Agriculture, Bheemarayanagudi and UAS, GKVK, Bengaluru to estimate the combining ability and investigate gene action involved in inheritance of yield and its components traits of maize inbreds through 20×20 full diallel cross analysis. 380 SCHs synthesized through full diallel mating design were evaluated in simple lattice square lattice design at two locations. Analysis of variance revealed significant differences among the hybrids, parents v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
5
4
0
Order By: Relevance
“…Combining studies for physiological and yield traits in maize Yazachew et al (2017). Results on gca effects revealed that the two lines Early yellow (P 1 ) and line POP-445 (P 2 ) exhibited good general combiners in all three environments.The gca effect for days to 50% silking were observed to vary from -0.88** (Early yellow) to -0.69** (POP -31 Q2) in E 1, from-1.43** (Early yellow) to-0.48** (POP -31 Q2) in E 2 , and from -1.07** (Early yellow) to -0.23 (CML -359) in E 3 .Similar results were observed by Kumar et al (2022). General combining ability results revealed that Early yellow (P 1 ), line POP-445 (P 2 ) showed significant desirable negative gca effects for days to 50% maturity in all environments while line POP -31 Q2 (P 3 ) showed negative gca effect in E 2 and E 3 respectively.Thegca effect for days to 50% maturity were observed to vary from -1.43** (Early yellow) to -0.68* (CML -359) in E 1, from-1.78** (Early yellow) to -0.96* (POP-445) in E 2 , and from -2.12** (Early yellow) to -1.62** (POP -31 Q2) in E 3.…”
Section: General Combining Ability Effect In Maize Parents Across Env...supporting
confidence: 84%
See 3 more Smart Citations
“…Combining studies for physiological and yield traits in maize Yazachew et al (2017). Results on gca effects revealed that the two lines Early yellow (P 1 ) and line POP-445 (P 2 ) exhibited good general combiners in all three environments.The gca effect for days to 50% silking were observed to vary from -0.88** (Early yellow) to -0.69** (POP -31 Q2) in E 1, from-1.43** (Early yellow) to-0.48** (POP -31 Q2) in E 2 , and from -1.07** (Early yellow) to -0.23 (CML -359) in E 3 .Similar results were observed by Kumar et al (2022). General combining ability results revealed that Early yellow (P 1 ), line POP-445 (P 2 ) showed significant desirable negative gca effects for days to 50% maturity in all environments while line POP -31 Q2 (P 3 ) showed negative gca effect in E 2 and E 3 respectively.Thegca effect for days to 50% maturity were observed to vary from -1.43** (Early yellow) to -0.68* (CML -359) in E 1, from-1.78** (Early yellow) to -0.96* (POP-445) in E 2 , and from -2.12** (Early yellow) to -1.62** (POP -31 Q2) in E 3.…”
Section: General Combining Ability Effect In Maize Parents Across Env...supporting
confidence: 84%
“…Results (Table 1) revealed that the parents, Early yellow (P 1 ) and line POP-445 (P 2 ) were found as good general combiners in all three environments E 1 , E 2 and E 3 for earliness in tassel The gca effect for days to 50% tasseling were observed to vary from -0.91** (Early yellow) to -0.66** (POP -31 Q2) in E 1, from-1.38** (Early yellow) to -0.47** (POP -31 Q2) in E 2 , and from -1.01** (Early yellow and POP-445) to -0.23 (CML -359 and CM-124) in E 3 .Similar results were observed by Kumar et al(2022) and…”
Section: General Combining Ability Effect In Maize Parents Across Env...supporting
confidence: 83%
See 2 more Smart Citations
“…From the general combining ability study, the parents HKI-193-2 (P 10 )LM 13(P 6 ) and line CM 129 (P 5 ) were found to be good general combiners of this trait as they exhibited significant positive gca effects in environments.The gca effect for grain yield per plant varied from 0.45 (CM-124) to 8.52** (LM 13) in E 1, from 0.89 ** (DMR QPM-28) to 7.35 ** (LM 13) in E 2 , and from 0.44 ** (POP-445) to 5.97 **(LM 13) in E 3. The results were supported by the findings of Sumalini et al (2015) and Kumar et al (2022). Study on gca effects reveal that the parental line HKI-193-2 (P 10 )showed significant positive gca effects in all environments , while the line LM 13 (P 6 ) and POP-445 (P 2 ) in environments E 1 and E 2 making them as suitable good combiners for the trait.…”
Section: General Combining Ability Effect In Maize Parents Across Env...supporting
confidence: 69%